Inhibition of Tumor Angiogenesis by a Synthetic Cell‐adhesive Polypeptide Containing the Arg‐Gly‐Asp (RGD) Sequence of Fibronectin, Poly(RGD) - Saiki, Ikuo (Jpn J Cancer Res, 1990)
We have investigated the anti‐angiogenic effect of a polymeric peptide based on the Arg‐Gly‐Asp (RGD) core sequence of fibronectin as a monomer unit, i.e., poly(RGD), in syngeneic mice and in vitro. Single intratumoral administration of poly(RGD) on day 0, 1 or 7 after tumor implantation achieved a significant reduction of B16‐BL6 melanoma colonization in the lungs, but did not affect the size of the primary tumor at the time of amputation. The number of capillary blood vessels oriented toward the tumor mass increased during the early growth phase after the intradermal inoculation of the tumor. Poly(RGD) significantly inhibited the formation of tumor neovascularization when co‐injected with the tumor cells or separately injected intratumorally or intravenously on day 1 or 3 after tumor inoculation. This inhibitory effect of poly(RGD) was dose‐dependent. Poly(RGD) was able to inhibit the haptotactic migration of endothelial cells along a gradient of substratum‐immobilized fibronectin but not laminin. Tumor‐conditioned medium (CM) by itself did not act as a chemoattractant when it was added in the lower compartment of a Transwell chamber, but promoted the endothelial cell migration to immobilized fibronectin or laminin. Poly(RGD) inhibited the enhanced cell migration to fibronectin but not to laminin in response to CM. Thus, poly(RGD)‐mediated inhibition of tumor metastasis may be partly due to the inhibition of tumor‐induced angiogenesis at primary and secondary sites.